2018
DOI: 10.3390/su11010055
|View full text |Cite
|
Sign up to set email alerts
|

Regional Temporal and Spatial Trends in Drought and Flood Disasters in China and Assessment of Economic Losses in Recent Years

Abstract: Understanding the temporal and spatial distribution in disasters plays an important role in disaster risk management. The present study aims to explore the long-term trends in drought and floods over China and estimate the economic losses they cause. A peak-over-threshold approach is used to identify flood peaks, and the relationship between the disasters and climate indices is investigated using Poisson regression. The major results are as follows: (1) the northeastern part of China was severely affected by d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 44 publications
0
20
0
Order By: Relevance
“…Precipitation is the main causing factor of flood. Many scholars have done research on the relationship between precipitation feature and flood [4,5,6,7]. Pielke presented a conceptual framework which assessed the role that variability in precipitation had in damaging flooding in the United States at national and regional levels [8]; Hartmann suggested that strong monsoon precipitation in the arid high mountainous regions played a major role in the 2010 floods in Pakistan [9].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitation is the main causing factor of flood. Many scholars have done research on the relationship between precipitation feature and flood [4,5,6,7]. Pielke presented a conceptual framework which assessed the role that variability in precipitation had in damaging flooding in the United States at national and regional levels [8]; Hartmann suggested that strong monsoon precipitation in the arid high mountainous regions played a major role in the 2010 floods in Pakistan [9].…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity analysis of the flash floods to GDP is important for sustainable socioeconomic development. The phenomenon of sensitivity rising can influence many development issues, including an imbalance in regional structures and tourism damage [61,62]. The results of our sensitivity analysis showed that all regions were non-sensitive during 1995-2000 (Figure 7a).…”
Section: Sensitivity Analysis Of the Flash Floods To Economic Developmentmentioning
confidence: 89%
“…Among the various adverse effects of drought, its influence on agriculture is the most significant and direct. In China, annual direct economic losses to agriculture from drought were approximately 32 billion yuan in the period from 1949 to 2013 (Chou et al 2019). Under drought stress, plants display various morphological (e.g., reduced leaf area), physiological (e.g., water-use efficiency and stomatal movement), and biochemical (e.g., accumulation of osmolytes and enzymatic and non-enzymatic antioxidants) characteristics (Fang & Xiong 2015).…”
Section: Improved Drought Stress Tolerance In Higher Plants Using Thementioning
confidence: 99%